Image-Based Proxy Accumulation for Real-Time Soft Global Illumination - Sloan, Peter-Pike; Govindaraju, Naga; Nowrouzezahrai, Derek; Snyder, John (Pacific Graphics, 97-105, October 2007., 2007)
We present a new, general, and real-time technique for soft global illumination in low-frequency environmental lighting. It accumulates over relatively few spherical proxies which approximate the light blocking and re-radiating effect of dynamic geometry. Soft shadows are computed by accumulating log visibility vectors for each sphere proxy as seen by each receiver point. Inter-reflections are computed by accumulating vectors representing the proxy’s unshadowed radiance when illuminated by the environment. Both vectors capture low-frequency directional dependence using the spherical harmonic basis. We also present a new proxy accumulation strategy that splats each proxy to receiver pixels in image space to collect its shadowing and indirect lighting contribution. Our soft GI rendering pipeline unifies direct and indirect soft effects with a simple accumulation strategy that maps entirely to the GPU and outperforms previous vertex-based methods. All sequences computed on Nvidia 8800GTX and 2.4ghz Intel Core2Duo. FightBilateral.avi : compares bilateral upsampling at various resolutions with shading at display resolution. 1x (shading at display res. 512x512) -> 31fps 4x (bilateral upsampling from 256x256) -> 84fps 16x (bilateral upsampling from 128x128) -> 160fps 64x (bilateral upsampling from 64x64) -> 176fps FightProgression.avi : shows how various global illumination effects animate. AcrobatsNice.avi : real-time results recorded from scene containing up to 20 tumbling/walking characters. frame rate with all 20 characters -> 85 fps FightNice.avi : real-time results recorded from fight scene. frame rate -> 84 fps https://youtu.be/unM30U0405Y https://youtu.be/E4d8OwxFaYM https://youtu.be/bBRE3kV2zzk https://youtu.be/hcfYTX0YmTI https://youtu.be/dReXX7Q-oJU https://youtu.be/aMxEnimlZ1g